2001
DOI: 10.1144/qjegh.34.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the durability of mudrocks using the modified jar slake index test

Abstract: As exposure to weathering processes or other changes in moisture content can be the cause of troublesome breakdown of many mudrocks, it is essential to have reliable means of predicting this behaviour. Although the ISRM slake durability test is the standard test used to distinguish between durable and non-durable mudrocks, the test does not always identify problematic materials. The dynamic nature of the test and the use of an arbitrary 2 mm drum mesh size are particular short falls. The test is too aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Moreover, the test also employs a tumbling factor, which generally does not exist in the field. Meanwhile, it is surprising that there is no specified testing procedure for a static slaking test even though a number of experiments have been carried out, such as the ones performed by Morgenstern and Eigenbrod (1974), Wood andDeo (1975), Venter (1981), Ichinose and Matsui (1989), Santi (1998), Czerewko and Cripps (2001) and Sadisun et al (2002a). In general, the static slaking tests provide simple and reliable tests when the standard slake durability test is impermissible, particularly for medium to very weak rock materials (Sadisun et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the test also employs a tumbling factor, which generally does not exist in the field. Meanwhile, it is surprising that there is no specified testing procedure for a static slaking test even though a number of experiments have been carried out, such as the ones performed by Morgenstern and Eigenbrod (1974), Wood andDeo (1975), Venter (1981), Ichinose and Matsui (1989), Santi (1998), Czerewko and Cripps (2001) and Sadisun et al (2002a). In general, the static slaking tests provide simple and reliable tests when the standard slake durability test is impermissible, particularly for medium to very weak rock materials (Sadisun et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The main problem with the slake durability index test according to various researchers (Czerewko and Cripps, 2001;Erguler and Shakoor, 2009and Richardson and Long, 1987, Moon and Beattie, 1995 is that the test is not efficient in differentiating durable from non-durable mudrocks ( Figure 2). This is mainly because of the 2 mm mesh size which may retain a large portion of slaked material even for non-durable rocks…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been shown by Czerewko & Cripps (2001) that the standard slake durability test lacks sensitivity when it is used to distinguish between durable and non-durable mudrocks. This is due to the inherent bias possessed by the equipment used for the test, as an arbitrary 2mm mesh size is used to distinguish between slaked and non-slaked material.…”
Section: Causementioning
confidence: 99%
“…It was found that the modified jar slake index (Czerewko & Cripps, 2001) provides an additional means of textural classification since the test monitors the extent of microfracture development. Fracture distribution counts were carried out on sections cut perpendicular and parallel to bedding.…”
Section: Textural Analysismentioning
confidence: 99%